Dilated cardiomyopathy caused by mutation of the PNPLA2 gene: a case report and literature review - Wang, Shuai; Wu, Sha; Peng, Daoquan (Frontiers in Genetics, 2024)
Deficiency of adipose triglyceride lipase (ATGL) due to mutation in PNPLA2 causes autosomal recessive disease neutral lipid storage disease with myopathy (NLSDM) (MIM: #610717). NLSDM patients are mainly affected by progressive myopathy, cardiomyopathy and hepatomegaly. Cardiac involvement was reported in 40-50% of NLSDM patients. Patients with cardiac involvement have adult-onset progressive heart failure, mimicking dilated or hypertrophic cardiomyopathy. The clinical characteristics, genotype-phenotype correlation, and prognosis of cardiomyopathy secondary to PNPLA2 mutation are not understood. We reported two male patients carrying homozygous splicing mutation NM_020376.4 (c.757+1G>T) in PNPLA2, presenting with severe dilated cardiomyopathy and mild skeletal muscle involvement. Through literature review, the ECG and imaging feature as well as prognosis of 49 previously reported cases of cardiomyopathy caused by PNPLA2 mutation were summarized. This study suggests NLSDM should be considered as a cause of cardiomyopathy, especially those with elevated CK levels regardless of whether symptoms such as muscle weakness or atrophy are present.